The Expected (Signaling) Value of Higher Education - Laura Ehrmantraut; Pia Pinger; Renske Stans (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper explores students' expectations about the returns to completing higher education and provides first evidence on perceived signaling and human capital effects. We elicit counterfactual labor market expectations for the hypothetical scenarios of leaving university with or without a degree certificate among a large and diverse sample of students at different stages of higher education. Our findings indicate substantial perceived returns to higher education. Moreover, using within-individual fixed effects models, we document substantial expected labor market returns from signaling, whereas perceived productivity-enhancing (human capital) returns seem to be less pronounced. Over the expected course of career, we find lasting education premia as well as evidence consistent with employer learning.
Keywords: I21; I23; I26; J24; J31; J32; J44; 330; higher education; returns to education; signaling; educational attainment; licensing; employer learning